THE EXPECTED DEMOGRAPHIC INFLUENCES ON THE PROVISION OF EDUCATION SERVICES IN THE NEIGHBOURHOODS OF RIGA - Apsite-Berina, Elina; Paiders, Juris; Dahs, Aleksandrs; Berzins, Maris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This paper discusses the spatial extent of population change and provides new insights into the relationships between demographic characteristics and the provision of education services in urban neighbourhoods of Riga. Thus, our empirical evidence confirms that the provision of social infrastructure is fundamentally dependent on the nature of demographic processes. The aim of this paper is twofold: to explore the spatial extent of changes in the number of pre-school and school-aged children in Riga, and to assess how the demographic change of particular age cohorts are associated with the provision of educational establishments at the neighbourhood level. Using available statistics and based on calculations, this article reveals how the interplay between demographic and education related characteristics could be used in the analysis of particular age groups. The main findings show that educational institutions in capital city are distributed unevenly. Similarly, there is a great variety in demographic development between the urban neighbourhoods of Riga. Thus, unmatched demand for educational facilities or lacking specific types of institutions altogether create additional load in the neighbourhoods of inner-city, while increasing daily mobility of children and their parents.